Thermal characteristics and recycling of bolus – a polyurethane-based material used in radiotherap - Worzakowska, Marta; Szajnecki, Łukasz; Tarasiuk, Bogdan; Kozłowska, Aleksandra; Podkościelna, Beata (Polimery, 2024)
The thermal resistance was investigated and the potential for recycling of a polyurethanebased polymer material (bolus) in the form of a gel constituting medical waste after irradiation with ionizing energy was indicated. The same gel, which was not subjected to radiotherapy, was used as a reference material. Thermal stability, the course of oxidative decomposition and the type of volatile substances released during heating in an oxidizing atmosphere were examined using the TG/FT-IR method. The glass transition temperature (Tg) of the tested materials before and after irradiation was determined using the DSC method. It was found that irradiation caused a slight change in Tg and increased thermal stability. However, the irradiation time had no effect on the type of gaseous decomposition products released during heating in an oxidizing atmosphere. The used polyurethane material (bolus) was recycled to obtain new composite materials with different physicochemical properties.